Diversity of Araceae in Marai Parai Transect Line, Kinabalu Park, Sabah - Rasyidah Wahab; Kartini Saibeh (Sabah Parks Nature Journal, 2024)
The Araceae is one of the plant families that can be found in the Kinabalu Park area, which has a diverse number of species. This study aims to observe the species diversity of Araceae along the main route from Kinapasuwon (which is located in Kiau) to Marai Parai, and from Marai Parai to Suminungkad. The transect sampling method with a width of 2 metres on both sides of the transect was carried out on the main route, based on five different pit stop; Kiau – Kem Lanting (T1) (850 - 1010 m.a.s.l.), Kem Lanting – Kinotoki (T2) (1010 – 1420 m.a.s.l.), Kinotoki – Marai Parai (T3) (1420 - 1530 m.a.s.l.), Marai Parai – Suminungkad (T4) (1530 - 1800 m.a.s.l.), and Kem Nunuk – Kinotoki (T5) (1010 – 1530 m.a.s.l.). From the observations, 13 genera were identified along the transect: Alocasia, Amorphophallus, Amydrium, Arisaema, Bucephalandra, Colocasia, Homalomena, Nabalu, Ooia, Pothos, Rhaphidophora, Schismatoglottis, and Scindapsus. The Kiau – Kem Lanting transect at an altitude of 850 – 1010 metres above sea level showed the highest species diversity of Araceae. Similarity analysis conducted indicated that the transects have low similarity in Araceae species. Therefore, the main route to Marai Parai via Kiau has a unique and high diversity of Araceae species, which is distinct based on altitude differences.